2012
DOI: 10.1038/cdd.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical control of C. elegans germline apoptosis by the insulin/IGF-1 and Ras/MAPK signaling pathways

Abstract: The insulin/IGF-1 pathway controls a number of physiological processes in the nematode worm Caenorhabditis elegans, including development, aging and stress response. We previously found that the Akt/PKB ortholog AKT-1 dampens the apoptotic response to genotoxic stress in the germline by negatively regulating the p53-like transcription factor CEP-1. Here, we report unexpected rearrangements to the insulin/IGF-1 pathway, whereby the insulin-like receptor DAF-2 and 3-phosphoinositidedependent protein kinase PDK-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…We found that levels of PA were unaffected by daf-2(m577) but reduced by daf-2(e1370) (Supplementary Figure 7A, 7B). The observed effect of daf-2(e1370) is consistent with a previous study [39], though another report described increased germline apoptosis in daf-2(e1370) mutants [40]. Other pathways have also been shown to influence C. elegans reproductive aging, particularly TGF-β Sma/Mab signalling [18, 41, 42].…”
Section: Resultssupporting
confidence: 88%
“…We found that levels of PA were unaffected by daf-2(m577) but reduced by daf-2(e1370) (Supplementary Figure 7A, 7B). The observed effect of daf-2(e1370) is consistent with a previous study [39], though another report described increased germline apoptosis in daf-2(e1370) mutants [40]. Other pathways have also been shown to influence C. elegans reproductive aging, particularly TGF-β Sma/Mab signalling [18, 41, 42].…”
Section: Resultssupporting
confidence: 88%
“…Of course, an additional interpretation of our findings is that Smk1 may also participate directly in promoting PCD. Intriguingly, the MAP kinase gene mpk-1 positively regulates apoptosis-like death of immature germ cells in the syncytial Caenorhabditis elegans gonad in a phenomenon that is conceptually similar to yeast meiotic mother cell death (42,43). Further exploration of the control mechanisms by which Smk1 impacts meiotic PCD will illuminate these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C is an important signaling molecule in mediating tumor cell adhesion,movement,and invasion,and a PKC suppressor has displayed anti-invasion characteristics in vitro and in vivo experiments. As a special domain of PLCE1, the CDC25-like domain could change the molecular structure of Ras family via acting on guanosine triphosphate exchange factor (GEF), and activate the Ras/MAPK signaling pathways (Cui et al, 2013) and then regulate cell apoptosis and growth, promotes cell proliferation, differentiation and even malignant change (Perrin et al, 2013). Ada-Nguema AS (Ada-Nguema et al, 2006) found that phospholipase Cε (PLCε) is a novel R-Ras effector mediating the effects of R-Ras on the actin cytoskeleton and membrane protrusion, because R-Ras was coprecipitated with PLC ε and increased its activity (Martins et al, 2014).…”
Section: Discussionmentioning
confidence: 99%